2016
DOI: 10.1002/bmb.20992
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing student retention of prerequisite knowledge through pre‐class activities and in‐class reinforcement

Abstract: To foster the connection between biochemistry and the supporting prerequisite concepts, a collection of activities that explicitly link general and organic chemistry concepts to biochemistry ideas was written and either assigned as pre-class work or as recitation activities. We assessed student learning gains after using these activities alone, or in combination with regularly-integrated clicker and discussion questions. Learning gains were determined from student performance on pre- and post-tests covering ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…This methodology restructures and reorders traditional lecture‐based (LB) approaches by moving students, rather than teachers, to the centre of learning . Such active learning should improve outcomes as learners practise with, engage with and apply their pre‐class learning . Although modern versions of the FC appeared over 10 years ago, and despite its popularity in education generally and medical education specifically, we lack firm conclusions regarding its efficacy …”
Section: Introductionmentioning
confidence: 99%
“…This methodology restructures and reorders traditional lecture‐based (LB) approaches by moving students, rather than teachers, to the centre of learning . Such active learning should improve outcomes as learners practise with, engage with and apply their pre‐class learning . Although modern versions of the FC appeared over 10 years ago, and despite its popularity in education generally and medical education specifically, we lack firm conclusions regarding its efficacy …”
Section: Introductionmentioning
confidence: 99%
“…Compared with the control group, which did not perform pre-class work and recitation activities, the group that did perform these scored higher. However, after 8 months, they reported that the learning effect was not maintained [14]. In our study, it was considered that the participants' knowledge was maintained to a certain extent until 6 months later, even if they attended a single program.…”
Section: Discussionmentioning
confidence: 63%
“…Retrieving information is important for the long‐term retention of content and developing the ability to use this information to resolve new problems that may be encountered . This can be achieved through activities that allow students to recall these concepts through solving clinical cases, answering case‐based questions, and creating concept maps.…”
Section: Discussionmentioning
confidence: 99%